Cobalt‐Catalyzed Transformation of Molecular Dinitrogen into Silylamine under Ambient Reaction Conditions. Issue 24 (5th May 2015) - Imayoshi, Ryuji; Tanaka, Hiromasa; Matsuo, Yuki; Yuki, Masahiro; Nakajima, Kazunari; Yoshizawa, Kazunari; Nishibayashi, Yoshiaki
Abstract The first successful example of cobalt‐catalyzed reduction of N2 with Me3SiCl and Na as a reductant, under ambient reaction conditions, gives N(SiMe3)3, which can be readily converted into NH3. In this reaction system, 2, 2′‐bipyridine (bpy) is found to work as an effective additive to improve substantially the catalytic activity. CoN2 complexes bearing three Me3Si groups as ancillary ligands are considered to work as key reactive species based on DFT calculations. The DFT results also allow the proposal of a detailed reaction pathway for the transformation of N2 into N(SiMe3)3.